2019
DOI: 10.1101/656264
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

White matter alterations in autism spectrum disorder and attention-deficit/hyperactivity disorder in relation to sensory profile

Abstract: Word Count words2 Abstract Background. Autism spectrum disorder (ASD) and attention deficit hyperactivity disorder (ADHD) have high rates of co-occurrence and share atypical behavioral characteristics, including sensory problems. The present diffusion tensor imaging (DTI) study was conducted to examine whether and how white matter abnormalities are observed in adult populations with developmental disabilities (DD) and to determine how brain-sensory relationships are either shared between or distinct to ASD … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…However, patients 5, 8, and 28 also have attention disorder. Furthermore, ASD, attention deficit, and ADHD have high rates of co-occurrence (Ohta et al, 2020). Therefore, the patient's ADHD might be caused by his ZNF462 genetic mutation.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients 5, 8, and 28 also have attention disorder. Furthermore, ASD, attention deficit, and ADHD have high rates of co-occurrence (Ohta et al, 2020). Therefore, the patient's ADHD might be caused by his ZNF462 genetic mutation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Owen et al reported among children with SPD a decreased FA and increased MD and RD, particularly in the posterior cingulate cortex (CC), corona radiata and thalamic radiations (Owen et al, 2013). Ohta and colleages reported that adults with autism spectrum disorder (ASD) and attention deficit hyperactivity disorder (ADHD) display a correlation between sensory sensitivity scores and RD in the posterior CC (Ohta et al, 2020). However, further research is needed to find objective measures that provide possible explanations for neural mechanisms underlying the linkage between sensory processing and psychopathology (Engel-Yeger et al, 2016b).…”
Section: The Neuroradiological Correlates Of Sensory Profilesmentioning
confidence: 99%
“…Despite the crucial importance of sensory processing in shaping normal and psychopathological behaviors, this topic is currently under investigated (Dunn et al, 2016). Indeed, the body of MRI research concerning sensory profiles is limited to few articles, mainly focused on young-aged, typically developed populations (Yoshimura et al, 2017;Shiotsu et al, 2021) and neurodevelopmental disorders (Owen et al, 2013;Ohta et al, 2020).…”
Section: Introduction 1sensory Processingmentioning
confidence: 99%